Case report: Efficacy of icotinib treatment in lung adenocarcinoma with esophageal squamous cell carcinoma: a rare case of double primary malignant tumors - Deng, Min; Li, Xiaoqing; Mu, Honghao; Wei, Man; Sun, Lan (Frontiers in Medicine, 2024)
Background Lung adenocarcinoma with esophageal squamous cell carcinoma is rare and the prognosis is poor, therefore there is an urgent need to improve this situation. The objective of this study was to explore the effect of first-generation tyrosine kinase inhibitors (TKIs) in the patient of the double primary malignant tumors. Case report We report a case of lung adenocarcinoma with esophageal squamous cell carcinoma treated by icotininb after five-year follow-up. A 71-year-old Chinese woman complaining of swallowing obstruction, heartburn, regurgitation of gastric acid for more than 2 months. An esophageal lesion was found by chest CT scans in T7 vertebral level. The diagnosis by gastroscopic biopsy was squamous cell carcinoma (SCC) with EGFR over-expression. Simultaneously, chest CT showed a 2 cm x 1 cm solitary lesion in the right superior pulmonary. The histological diagnosis by percutaneous lung Biopsy was “adenocarcinoma.” Epidermal growth factor receptor (EGFR) gene mutation status was evaluated by Sanger sequencing, and an exon 21 point mutation (L858R) was identified. When the double primary malignant tumors were diagnosed, the patient refused operation and received a tyrosine kinase inhibitor (TKI), icotinib, at the dose of 125 mg, three times per day. All serum tumor biomarkers such as CEA and cancer antigen 125 (CA125) were in the normal range during the treatment period. After five-year follow-up, the patient has no evidence of recurrence or metastasis. The lung cancer was stable, meanwhile the esophageal lesion was almost cured. Conclusion Icotininb is an effective treatment in the patients of the double primary malignant tumors of lung adenocarcinoma with EGFR gene mutation and esophageal squamous cell carcinoma with EGFR over-expression.